IMPLEMENTASI PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 34 TAHUN 2016 TENTANG KRITERIA KOTA ATAU KABUPATEN PEDULI HAK ASASI MANUSIA (Studi di Kota Surakarta) - Valencia, Natasha Olga; Firdausy, Adriana Grahani (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This study examines and discusses the application of Regulation of the Minister of Justice and Human Rights Number 34 of 2016 on City Policy or District Concern for Human Rights. This research is a descriptive legal research that means or raises No. Regulation of the Minister of Justice and Human Rights Number 34 of 2016 on City Policy or District Concerned Human Rights with a qualitative approach. Types of data containing basic materials and secondary legal materials. Techniques used in document studies or interviews, interviews, and interviews. Data analysis techniques data reduction, data presentation, conclusions and verification. The results of this study are in the implementation of Surakarta City Cares for Human Rights for the right to health, the right to education, the rights to women and children, the right to population, the right to housing, and the right to a sustainable environment. The fulfillment of Surakarta City Concerning Human Rights is based on 1) appropriate indicators, structures and processes by filling in the data for documents required for the head of office that must endorse from the Head of the Regional or City Work Unit, the District Secretary or City, the Provincial Secretary discusses and 2) inspections that include arithmetic, validity checks of data identified by marks of approval by the head of the Regional Administrative Work Unit and relevant agencies, the validity of data and supporting documents indicated by the signature of the Regional Secretariat of the Regency or City.